Indigenous Language Speaking Students Learning Mathematics in English: Expectations of and for Teachers - Edmonds-Wathen, Cris (The Australian Journal of Indigenous Education, 2015)
Effective mathematics teaching for Indigenous language speaking students needs to be based on fair expectations of both students and teachers. Concepts of ‘age-appropriate learning’ and ‘school readiness’ structure assessment expectations that entire cohorts of Indigenous language speaking students are unable to meet. This institutionalises both student and teacher failure, as both are exhorted to meet unachievable expectations. The voices of teachers teaching in a very remote school provide insight into teachers’ responses to the mismatch between the system expectations and the teaching context. Teacher interviews in a small Northern Territory school, conducted within an ethnographic study, showed that teachers’ decisions regarding the level of mathematics curriculum taught were informed by students’ prior learning and by the language dynamic in their classrooms. The need and pressure to teach Standard Australian English also affected how mathematics was taught. This leads to a reformulation of the concept of school readiness to ask how schools can be more ready for their Indigenous language speaking students in terms of preparing and supporting teachers.